HIPR: Hardware IP Protection through Low-Overhead Fine-Grain Redaction - Aritra Dasgupta; Sudipta Paria; Swarup Bhunia (Transactions on Cryptographic Hardware and Embedded Systems)
Hardware intellectual property (IP) blocks have been subjected to various forms of confidentiality and integrity attacks in recent years due to the globalization of the semiconductor industry. System-on-chip (SoC) designers are now considering a zero-trust model for security, where an IP can be attacked at any stage of the manufacturing process for piracy, cloning, overproduction, or malicious alterations. Hardware redaction has emerged as a promising countermeasure to thwart confidentiality and integrity attacks by untrusted entities in the globally distributed supply chain. However, existing redaction techniques provide this security at high overhead costs, making them unsuitable for real-world implementation. In this paper, we propose HIPR, a fine-grain redaction methodology that is robust, scalable, and incurs significantly lower overhead compared to existing redaction techniques. HIPR redacts security-critical Boolean and sequential logic from the hardware design, performs interconnect randomization, and employs multiple overhead optimization steps to reduce overhead costs. We evaluate HIPR on open-source benchmarks and reduce area overheads by 1 to 2 orders of magnitude compared to state-of-the-art redaction techniques without compromising security. We also demonstrate that the redaction performed by HIPR is resilient against conventional functional and structural attacks on hardware IPs. The redacted test IPs used to evaluate HIPR are available at: https://github.com/UF-Nelms-IoT-Git-Projects/HIPR.